Oil Price Volatility and Equity Valuation of Listed Energy Companies in Nigeria: A Panel ARDL Model - Okodua, Henry; Urhie, Ese; Erhi, Moses Akpesiri; Hassan, Christiana Onyohu; Fasanu, Eyitemi Ayomikun (International Journal of Energy Economics and Policy, 2022)
The study investigates the nexus between oil price volatility and market valuation of listed energy companies in Nigeria, within a dynamic heterogeneous panel model framework. The paper utilizes the pooled mean group estimator in analysing the hypothesized relationship among equity valuation of listed energy companies in Nigeria, oil price volatility, and two control variables – firm profitability and inflation rate. The overwhelming weight of the evidence emerging from key findings of the study indicates that a distinct difference exists between the short-run impact of oil price volatility on the equity valuation of oil firms in Nigeria from the long-run impacts. While the short-run results show a mix of negative and positive, but statistically significant impacts of oil price volatility on equity valuation across listed oil firms, the long-run results indicate a statistically significant positive impact of oil price volatility on the stock valuation of energy firms in Nigeria. The short-run results are highly suggestive of the important role of the level of risk investors are willing to accommodate in their decisions to invest in stocks under different economic scenarios, in explaining stock returns for each of the oil-producing firms in Nigeria. The paper concludes that the risk premium investors place on stocks of oil companies is central in explaining the short-run impact of oil price volatility on the equity valuation of oil firms in Nigeria.